Visualization of Trna Movements on the Escherichia coli 70s Ribosome during the Elongation Cycle - Agrawal, Rajendra K. (The Rockefeller University Press, 2000)
Three-dimensional cryomaps have been reconstructed for tRNA–ribosome complexes in pre- and posttranslocational states at 17-Å resolution. The positions of tRNAs in the A and P sites in the pretranslocational complexes and in the P and E sites in the posttranslocational complexes have been determined. Of these, the P-site tRNA position is the same as seen earlier in the initiation-like fMet-tRNA(f) (Met)-ribosome complex, where it was visualized with high accuracy. Now, the positions of the A- and E-site tRNAs are determined with similar accuracy. The positions of the CCA end of the tRNAs at the A site are different before and after peptide bond formation. The relative positions of anticodons of P- and E-site tRNAs in the posttranslocational state are such that a codon–anticodon interaction at the E site appears feasible.